Prevention Strategies for Policing Gun Violence. Issue 1 (November 2022) - Braga, Anthony A.; Cook, Philip J.; Douglas, Stephen
The police have the unique capacity to preempt and deter violence and to reduce the use of firearms in violent encounters. But overly aggressive policing tactics have contributed to a fraught relationship with low-income minority communities in which gun violence is heavily concentrated. Increased resources should be devoted to policing gun violence, but efforts of this sort must be targeted and disciplined. Effective policing requires a focus on the places and people that are at greatest risk; and there is a strong case for police agencies to increase the resources devoted to investigations of all criminal shootings, not just homicides. Successful policing of gun violence requires a productive working relationship with victims and their neighbors, which can be facilitated through observing community policing principles and respect for residents' interests.